Removal of Lead(II) Ions by Adsorption ontoBamboo Dust and Commercial Activated Carbons -A Comparative Study - N. Kannan; T. Veemaraj (E-Journal of Chemistry)
Studies on the removal of lead(II) ions by adsorption onto indigenously prepared bamboo dust carbon (BDC) and commercial activated carbon (CAC) have been carried out with an aim to obtain data for treating effluents from metal processing and metal finishing industries. Effect of various process parameters has been investigated by following the batch adsorption technique at 30±1°C. Percentage removal of lead(II) ions increased with the decrease in initial concentration and increased with increase in contact time and dose of adsorbent. Amount of lead(II) ions adsorbed increases with the decrease in particle size of the adsorbent. As initial pH of the slurry increased, the percentage removal increased, reached a maximum and the final solution pH after adsorption decreases. Adsorption data were modeled with the Freundlich and Langmuir isotherms, the first order kinetic equations proposed by Natarajan – Khalaf, Lagergren and Bhattacharya and Venkobachar and intra- particle diffusion model and the models were found to be applicable. Kinetics of adsorption is observed to be first order with intra-particle diffusion as one of the rate determining steps. Removal of lead(II) ions by bamboo dust carbon (BDC) is found to be favourable and hence BDC could be employed as an alternative adsorbent to commercial activated carbon (CAC) for effluent treatment, especially for the removal of lead(II) ions